Fiscal Autonomy and Tax Morale: Evidence from Germany - Benno Torgler; Jan Werner (Center for Research in Economics, Management and the Arts (CREMA), 2005)
This paper analyses fiscal autonomy in Germany. First, it provides an overview of fiscal autonomy. What is novel in this paper compared to previous studies is the development of a fiscal autonomy coefficient for the states, based on communal data. The basic intention in the empirical part is to analyse how fiscal autonomy affects tax morale, defined as the intrinsic motivation to pay taxes, in Germany. Strong evidence has been found that a higher fiscal autonomy leads to a higher tax morale, controlling in a multivariate analysis for additional factors. Thus, this paper fills a gap in the tax compliance literature, which has rarely analysed the impact of fiscal autonomy on compliance
Keywords: H26; H73; D70; 330; Tax Morale; Tax Compliance; Fiscal Autonomy; Germany